Novel beginnings : experiments in eighteenth-century English fiction - Spacks, Patricia Meyer (Yale guides to English literature., 2006)
This fresh account of eighteenth-century English fiction departs from the traditional focus on the realistic novel to emphasise the many kinds of experimentation that marked the genre before the conventions of the novel were firmly established. Treating well-known works like "Tom Jones" and "Tristram Shandy" in conjunction with less familiar texts like "Sarah Fielding's: The Cry" and "Jane Barker's: A Patchwork Screen for the Ladies", this book evokes the excitement of a multifaceted and unpredictable process of growth and change. Investigating fiction throughout the 1700s, Patricia Meyer Spacks delineates the individuality of specific texts while also suggesting connections among novels. She sketches a wide range of forms and themes, including Providential narrative, psychological thriller, political roman a clef, sentimental parable, political allegory, Gothic romance and many others. These multiple narrative experiments show the impossibility of thinking of eighteenth-century fiction simply as a precursor to the nineteenth-century novel, Spacks shows. Instead, the vast variety of engagements with the problems of creating fiction demonstrates that literary history - by no means inexorable - might have taken quite a different course